2019
DOI: 10.1017/s0144686x19001569
|View full text |Cite
|
Sign up to set email alerts
|

Constructing and negotiating social participation in old age: experiences of older adults living in urban environments in the United Kingdom

Abstract: The age-friendly cities and communities movement has focused on how to better support older adults to age well within urban environments. Central to 'ageing well' and 'active ageing' agendas is ensuring that older adults can participate in meaningful forms of social participation. The benefits of social participation in old age have been well documented, and research amongst communitydwelling older adults has explored some of the neighbourhood qualities that facilitate or impede such forms of engagement. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 38 publications
1
29
0
3
Order By: Relevance
“…Two indicators are recommended: access to community centres and neighbourhood houses; and access to recreational services that cater to the needs of older people. Shared or ‘third spaces’ such as these are critical social infrastructure [ 25 ] and essential in supporting social participation for older adults [ 93 ]. Recreational services also support physical and mental health through opportunities for physical activity designed for older people and supporting community connections.…”
Section: Social Participationmentioning
confidence: 99%
“…Two indicators are recommended: access to community centres and neighbourhood houses; and access to recreational services that cater to the needs of older people. Shared or ‘third spaces’ such as these are critical social infrastructure [ 25 ] and essential in supporting social participation for older adults [ 93 ]. Recreational services also support physical and mental health through opportunities for physical activity designed for older people and supporting community connections.…”
Section: Social Participationmentioning
confidence: 99%
“…In addressing inequality of opportunity there has been a focus on combatting social disadvantage, facilitating social wellbeing, and enabling continuing contributions to the communities in which people live (Kendig and Browning, 2010). Yet being able to take advantage of those opportunities is often complex for older people, and research has identified the difficulties in older people negotiating access to those supports (Woolrych et al, 2019). For example, a community may seemingly be agefriendly when mapping assets and resources, but this does not translate into ease of everyday use for older people.…”
Section: Ageing Urban Environments and Inequalitymentioning
confidence: 99%
“…For e.g. we know that older adults often adopt protective responses in times of adversity, they negotiate their built environment in unanticipated ways and they assume active roles within their community at times of transformation and change (Woolrych et al, 2019;Makita et al 2020). Age-friendly cities and communities need to create the opportunities for more citizen-led movements which enable a framework for positive change even when that coordination might be lacking at a government and formal institutional level.…”
Section: Participation and Equality In Age-friendly Citiesmentioning
confidence: 99%
“…In response to this, the ageing-in-place agenda has become focused on how older adults can be supported to live at home and in their community, where they can remain active, engaged, socially connected, and independent (Peace et al, 2011). Contemporary urban cities can be ‘unfriendly’ and ‘hostile’ to older adults, acting as a barrier to accessing social, economic and civic opportunities, and putting older adults at risk for isolation and loneliness (Scharf et al, 2005; Woolrych et al, 2019). In addressing this, international policy and practice has focused on the creation of age-friendly cities and communities as environments to encourage active ageing through mobility, respect and social inclusion, transport, housing, safety, and security (Buffel et al, 2018).…”
mentioning
confidence: 99%